The Real Time Monitoring System and Early Detection of Unbalanced Load for the Three Phase Distribution Systems in Urban Areas - Syarifuddin Nojeng; Arif Jaya; Reny Murniati (International Journal Of Electrical Engineering and Inteligent Computing, 2023)
This paper introduces a three-phase unbalanced load condition monitoring system in a power distribution network that can monitor and provide early warning. The distribution system is a component of the power system that must always be observed in maintaining the service of delivering electricity to customers. Currently, many technologies are applied to the distribution system that can ensure the operation of the distribution network, especially distribution transformers to determine real-time transformer conditions so that damage and power losses can be minimized, but do not provide early detection. Therefore, the role of information technology is currently one of the investments that must be made for all electric power supply operators in maintaining the performance of distribution transformers through early detection. In this study, the system developed based on Internet of Things (IoT) technology that was built consists of: embedded system devices that function to carry out measurements and transmit data, Web Service software that functions to receive data from sensor systems, and Arduino-based software using the Blynk Cloud application platform in presenting data and managing data through Android display devices (HP/Laptop). The Blynk is a compatible platform for applications on Mobile OS (iOS and Android) in controlling Arduino, Raspberry Pi, or ESP8266-based modules, as well as similar modules via the Internet (IoT). This system was built to provide an early warning function against network parameter anomalies such as overload, overvoltage, and unbalanced load. After getting the data, the system will perform calculations to obtain recommendations for system optimization in the form of balancing, maintenance, or load maneuver. Based on testing, the time needed to send and receive notifications on smartphone users via the blynk application ranges from 3-4 seconds. By setting a tolerance limit of 20%, when the load is severely unbalanced where the neutral current is almost equal to or greater than the phase current, the local indicator light will light up and the Android system will provide an unbalanced load indicator.